Definition of a long-term energy policy for sustainable development in Peru - Luyo Kuong, Jaime (2009)
The importance of a long-term energy policy and planning is highlighted. For this purpose, first the successful Brazilian case and its macroeconomic repercussions are analyzed, then the current situation of the Peruvian energy sector, and, finally, a summary of an energy policy proposal that contributes to Peru's sustainable development is presented. Previously, a brief digression is made to comment on the participation and contribution of economists and engineers in the energy sector.